DOI: 10.14264/uql.2017.913
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Species Vulnerability to Climate Change in Tropical Asia: Implications for Biodiversity Conservation and Forest Management

Abstract: Global climate change is significantly altering the large scale distributions of plants and animals.The Earth has warmed by 0.7°C during the last century. The consequences are already apparent in forest ecosystems as species are responding to the changing climate with shifts in their phenology and geographic distributions. The potential for large increases in global mean temperatures (e.g., 4.3 ± 0.7°C) by 2100 has significant implications for forest species and ecosystems. Under these varying climatic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 167 publications
(360 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have indicated habitat loss and fragmentation from encroachment for settlements and farming were the principal threats to primates (Chetry et al., 2021 ). Climate change and land use/cover change could reduce suitable habitats for primates and increase their extinction risk (Carvalho et al., 2019 ; Deb, 2016 ). Fernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated habitat loss and fragmentation from encroachment for settlements and farming were the principal threats to primates (Chetry et al., 2021 ). Climate change and land use/cover change could reduce suitable habitats for primates and increase their extinction risk (Carvalho et al., 2019 ; Deb, 2016 ). Fernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…The centroid of habitat shifted to the southeast at a rate of approximately 2.84km/year from current to 2100. Previous studies have indicated that changes in annual precipitation, annual mean temperature, precipitation and temperature seasonality, as well as land use/ land cover changes, could reduce suitable habitat for the large mammals such as Asiatic black bear (Ursus thibetanus ), Asian elephant (Elephas maximus ) and western hoolock gibbon (Hoolock hoolock ), and thus increase their extinction risk (Deb, 2016). In addition, our results are consistent with the description that primates and other large mammals are highly dependent on a complete forest ecosystem for their food and security requirements, and habitat fragmentation will accelerate local population extinctions (Guan et al, 2022).…”
Section: Distribution Change In the Futurementioning
confidence: 99%
“…Climate change and its impact will vary among the region and countries although it is recognised as a global phenomenon [14]. Climate change studies in Tropical Asia are much deficient [15]. Diatom-based climate change studies are very scant in the tropical area.…”
Section: Mini Reviewmentioning
confidence: 99%